ACUTE DIETARY SALT MODULATION INDUCES CHANGES IN DYNAMICS OF MONOCYTES SUBSETS IN YOUNG HEALTHY WOMEN. (June 2018) - Rasic, L.; Drenjancevic, I.; Matic, A.; Stupin, M.; Novak, S.; Stupin, A.
Abstract : Objective: Our earlier studies have demonstrated that 7-days high-salt (HS) intake alters micro- and macrovascular response, and increases oxidative stress level in young healthy women independently of blood pressure (BP) changes. Still, it is not clarified whether such HS-induced endothelial dysfunction also involves changes in the immune system response which finally leads to vascular inflammation. Thus, the aim of this study was to assess the effect of 7-days salt intake modulation on monocyte subpopulations distribution and its activation in peripheral blood of young healthy women. Design and method: 15 young healthy women who all took 7-days low-salt (LS) diet (<3.2 g salt/day) followed by 7-days HS diet (∼14 g salt/day) participated in this study. Blood pressure (BP) was measured, and 24 h urine samples were analyzed for sodium, potassium, urea and creatinine levels before and after diet protocols. Flow cytometry analysis of circulating monocyte subpopulations distribution was assessed by determination of 'classical', 'non-classical' and 'inflammatory' monocytes based on CD14 and CD16 molecule expression in peripheral blood of young healthy women. Also, monocytes activation was assessed by measurement of lymphocyte function-associated antigen 1 (LFA-1, Cd 11a) expression which is known as ligand for endothelial cell adhesion molecules (ICAM-1). Results: Changes in 24 h urinary sodium confirmed subjects conformed to the diet protocol. There was no change in BP after HS diet. CD14+CD16++ gated (non-classical) monocytes from peripheral blood significantly decreased after HS diet compared to the LS diet. Distribution of CD14++CD16+ (intermediate) and CD14++CD16- (classical) gated monocytes from peripheral blood did not change after HS diet compared to the LS diet. CD11a expression on all three gated monocyte subpopulations was significantly decreased after HS diet compared to LS diet measurement. Conclusions: The results of the present study demonstrated that 7-days HS loading decreased CD14+CD16++ monocytes subpopulation (non-classical monocytes) which usually acts as endothelium housekeepers, and also decreased total monocytes (all three subpopulations) expressing high level of CD11a in young healthy women, probably due to activated monocytes adhesion and migration through endothelium layer to the place of endothelial injury.